The Impact of Varying Alginate Co-activation with Probiotics on the Artemia Bioencapsulation to Enhance Immunity Against Vibrio spp. - Suryono, Chrisna Adhi; Santoso, Adi; Yudiati, Ervia; Yulianto, Bambang; Sunaryo, Sunaryo; Azhar, Nuril; Alghazeer, Rabia (Marine Science Department Diponegoro University, 2024)
Alginate is known as an immunostimulant. The comprehensive study of Artemia on its co-activity with Lactobacillus bulgaricus resolves the relationship of feed digestibility, hematological parameters, gene expression, feed digestibility, and disease-resistant have not been covered. This study aimed to determine the effect of various doses alginate with Lactobacillus bulgaricus bio-encapsulated Artemia in Vibrio vulnificus, V. parahaemolyticus, and V. harveyi challenged. Alginate from Sargassum sp. L. bulgaricus were cultured and grown with de Man, Rogosa and Shape media. Nauplii Artemia was encapsulated for one hour with 400, 600, 800 ppm alginate doses, with and without probiotics. The Artemia then was challenged with three Vibrio spp. The Artemia mortality, immune parameters (Phenol Oxidase, Super-oxide Dismutase) were evaluated. Pro Phenol Oxidase, b-1,3-glucan-binding proteins (LGBP), and Lectin gene expression as well as gut evacuation time, fullness of gut were recorded. Compared to the non-probiotic alginate, co- probiotic activated and improved the mortality rate of 400 ppm alginate from 100% to 30-70% (36 h), CMI of 276-702, and mortality reduction (41.21-74.59%). The co-activity of 400 ppm alginate and L. bulgaricus resulted in higher PO and SOD activity. LGBP and proPO gene expression were also upregulated 233.44% and 185.17%. The gut evacuation time and fullness of alginate 400 ppm and L. bulgaricus treatment have also resulted in better performance than those of 800 ppm alginate without probiotics. Alginate and L. bulgaricus probiotics cooperated synergically through pre and probiotic mechanisms. This Artemia bio model defines that this combination will improve the survival rate, immune system, and gene expression. In the future this will be beneficial in terms of shrimp production in ponds.